Global and local mechanical properties control endonuclease reactivity of a DNA origami nanostructure. Issue 9 (11th February 2020) - Suma, Antonio; Stopar, Alex; Nicholson, Allen W; Castronovo, Matteo; Carnevale, Vincenzo
Abstract: We used coarse-grained molecular dynamics simulations to characterize the global and local mechanical properties of a DNA origami triangle nanostructure. The structure presents two metastable conformations separated by a free energy barrier that is lowered upon omission of four specific DNA staples (defect). In contrast, only one stable conformation is present upon removing eight staples. The metastability is explained in terms of the intrinsic conformations of the three trapezoidal substructures. We computationally modeled the local accessibility to endonucleases, to predict the reactivity of twenty sites, and found good agreement with the experimental data. We showed that global fluctuations affect local reactivity: the removal of the DNA staples increased the computed accessibility to a restriction enzyme, at sites as distant as 40 nm, due to an increase in global fluctuation. These results raise the intriguing possibility of the rational engineering of allosterically modulated DNA origami.